2008
DOI: 10.1111/j.1365-2354.2007.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of breast and cervical cancer risk factors and screening behaviours among nurses in rural region of Turkey

Abstract: Breast and cervical cancer are the most common causes of cancer mortality among women worldwide, but actually they are largely preventable diseases. There is limited data on breast and cervical cancer knowledge, screening practices and attitudes of nurses in Turkey. A self-administered questionnaire was used to investigate the knowledge and attitude of nurses on risk factors of the breast and cervical cancer as well as screening programmes such as breast self-examination (BSE), clinical breast examination, mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 33 publications
8
40
3
Order By: Relevance
“…In developed countries, nurses trained on the subject of cancer early diagnosis programmes have taken on an essential role in public health screening, and working in collaboration with health and social care personnel in training programmes (Tessaro and Herman, 2000;Ertem, 2008;Yaren et al, 2008). Nurses have responsibilities such as: providing the necessary information about early diagnosis and prevention of cervical cancer in women; encouraging high-risk families to undergo screening; conducting smear tests; and gathering and assessing data obtained from screening.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, nurses trained on the subject of cancer early diagnosis programmes have taken on an essential role in public health screening, and working in collaboration with health and social care personnel in training programmes (Tessaro and Herman, 2000;Ertem, 2008;Yaren et al, 2008). Nurses have responsibilities such as: providing the necessary information about early diagnosis and prevention of cervical cancer in women; encouraging high-risk families to undergo screening; conducting smear tests; and gathering and assessing data obtained from screening.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, nurses in this study had adequate knowledge about cervical cancer risk factors, other studies in Uganda, Turkey, Nigeria and Tanzania didn't shown the some findings [7][8][9][10]. This can be explained by the fact that our survey was conducted in the "training area" where most nurses have already taken training about cervical cancer in order to implement the early detection program.…”
Section: Discussionmentioning
confidence: 69%
“…Several studies regarding knowledge and practices of nurses on breast cancer prevention from Turkey (11)(12)(13)(17)(18)(19) and abroad (10,(20)(21)(22)(23)(24)(25)(26)(27) have showed significant differences in knowledge and application of BSE, CBE and mammography among nurses. These differences are thought to originate from research methodology, nurses' socio -demographic (age, education level, marital status, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies regarding the knowledge and practices of nurses on breast cancer prevention, and utilization of early diagnostic methods both from our country and abroad (10)(11)(12)(13)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, a comprehensive study on the effect of nurses' healthy lifestyle behaviors on the utilization of breast cancer early diagnosis methods was not found.…”
Section: Introductionmentioning
confidence: 99%